Vitamin D receptor is associated with prognostic characteristics of breast cancer after neoadjuvant chemotherapy—an observational study - Streb, Joanna; Łazarczyk, Agnieszka; Hałubiec, Przemysław; Streb-Smoleń, Anna; Ciuruś, Julita; Ulatowska-Białas, Magdalena; Trzeszcz, Martyna; Konopka, Kamil; Hodorowicz-Zaniewska, Diana; Szpor, Joanna (Frontiers in Oncology, 2024)
BackgroundBreast cancer (BC) is the most commonly diagnosed malignant tumor in women. The disease and its subsequent treatment pose a serious burden on the quality of life of patients. Neoadjuvant chemotherapy (NAC) has become one of the crucial strategies for the management of BC. Since the identification of the vitamin D receptor (VDR) in mammary tissues, extensive mechanistic research has been conducted on its function. The expression of VDR in BC cells and the tumor microenvironment could be a new prognostic factor for BC after NAC.Patients and MethodsThis observational, single-center study compared data from clinical and histopathological records of 111 female subjects with the expression of VDR in different cellular and tissue components of breast specimens obtained from surgery after NAC. VDR expression was evaluated using an immunoreactive score assigned after immunohistochemistry. Intergroup comparisons and logistic regression were used to identify associations between VDR expression and clinicopathological features of BC.ResultsWe found that the expression of VDR is associated with various clinical features (i.e., age, menopausal status, and NAC cycle number) and characteristics of prognostic significance, such as residual cancer burden class. Logistic regression analysis revealed that the expression of VDR in the nuclei and cytoplasm of surrounding normal mammary cells predicted vascular invasion and lymph node involvement.ConclusionsThe expression of VDR in tumor cells and their microenvironment is related to the clinicopathological characteristics of BC after NAC.